2015
DOI: 10.1080/15438627.2014.975807
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moderate and High Resistance Training Intensity on Indices of Inflammatory and Oxidative Stress

Abstract: This study was designed to examine the effect of moderate (MR) and high resistance (HR) training on systemic inflammation and circulating enzymatic antioxidant activity. Thirty males were assigned to HR (n = 10), MR (n = 10), or control (C; n = 10) groups. Resistance training was performed for eight weeks. Activities of superoxide dismutase (SOD), glutathione peroxidase (GPX), creatine kinase (CK), and concentrations of malondialdehyde (MDA), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 30 publications
4
40
2
4
Order By: Relevance
“…The current findings also support the speculation that intensity of exercise is a stronger predictor to OS responses as opposed to modality alone . Azizbeigi et al reported both moderate‐ and high‐intensity resistance training interventions are similarly effective at reducing markers of OS and inflammation for a period of 8 weeks . Although, it is important to note this intervention allowed one to 4 minutes of rest between sets; therefore, the suggestion of exercise intensity alone not being a significant predictor of antioxidant effects of chronic resistance exercise cannot be applied to a HIRE or CrossFit style protocol, such as the one currently utilized.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…The current findings also support the speculation that intensity of exercise is a stronger predictor to OS responses as opposed to modality alone . Azizbeigi et al reported both moderate‐ and high‐intensity resistance training interventions are similarly effective at reducing markers of OS and inflammation for a period of 8 weeks . Although, it is important to note this intervention allowed one to 4 minutes of rest between sets; therefore, the suggestion of exercise intensity alone not being a significant predictor of antioxidant effects of chronic resistance exercise cannot be applied to a HIRE or CrossFit style protocol, such as the one currently utilized.…”
Section: Discussionsupporting
confidence: 71%
“…This is not surprising since exercise-induced ROS accumulation is known to produce markers of OS and inflammation. 11,19 This is an especially meaningful finding since the exercise protocol only lasted on average between 5.4 and 6.6 minutes. This is also in agreement with our study design suggesting that intensity, as by its definition, is an appropriate tool for mediating ROS production.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations